Essential oil from the stem bark of Casuarina equisetifolia exhibits mosquitocidal potential - Adeosun, C.; Bamidele, I.; salau, B.; Ayorinde, A. (Journal of Phytopathology and Disease Management, 2017)
Mosquitoes are insects of medical importance. They are vectors of malarial parasites, arboviruses, filarial worms amongst others. Essential oils from some botanicals have been recognized with mosquitocidal potential. Various parts of the Casuarina equisetifolia plants have been reported to possess antihistaminic, antioxidant, antimicrobial properties but no study on the composition of the essential oil of its stem bark and its mosquitocidalÂ potential. The chemical composition of the essential oil from the stem bark of Casuarina equisetifolia was obtained by hydrodistillation and determined using gas chromatography-mass spectrometry. The mosquitocidal potential of the essential oil against Anopheles gambiae Â complex ( vectors of malarial parasites) and Aedes aegypti (vectors of arboviruses) mosquitoes was determinedÂ by bioassay using filter papers impregnated with the crude essential oil in World Health Organization exposure tubes. The KDT50 and KDT95 were calculated by means of log time-probit analysis.Â Nineteen compounds were identified with the major compounds beingÂ n-hexadecanoic acid (18.67%), cis-13-octadecanoic acid (17.83%), tridecane (11.84%), Undecane (10.45%), Hentriacontane (8.91%), Nonanal (8.62%) and Oxirane (2.43%). Fatty acids were observed to have the highest relative percentage (45.43%) followed by Aliphatic hydrocarbons (37.71%). The KdT50 of the essential oil against Anopheles gambiae complexÂ and Aedes aegypti was 40 minutes and 61 minutes while the KdT95Â wasÂ 129 minutes and 212minutes against Anopheles gambiae complexÂ and Aedes aegyptiÂ respectively. This essential oil with high percentage of fatty acids has significant mosquitocidal potential. This suggests the use of this botanical to control malaria and the arboviruses. The mosquitocidal potential of each constituent of the essential oil should be further explored.